2013
DOI: 10.1371/journal.pone.0056164
|View full text |Cite
|
Sign up to set email alerts
|

Binding of DC-SIGN to the Hemagglutinin of Influenza A Viruses Supports Virus Replication in DC-SIGN Expressing Cells

Abstract: Dendritic cells express lectins receptors, like DC-SIGN, which allow these cells to sense glycans that are present on various bacterial and viral pathogens. Interaction of DC-SIGN with carbohydrate moieties induces maturation of dendritic cells and promotes endocytosis of pathogens which is an important property of these professional antigen presenting cells. Uptake of pathogens by dendritic cells may lead to cross-presentation of antigens or infection of these cells, which ultimately results in activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
(52 reference statements)
2
46
0
Order By: Relevance
“…Although ␣2,3-or ␣2,6-linked sialic acid is considered the main IAV receptor and a key determinant for host and tissue tropism (44)(45)(46), sialidated-protein receptors are generally thought to facilitate virus entry (13). However, several lectin-type receptors (i.e., galactose-type lectin, mannose receptor, and DC-SIGN) that appear to bind IAV independently of sialic acid have been identified (47)(48)(49)(50). Accordingly, influenza virus can use multiple endocytic pathways to gain entry into host cells (7)(8)(9)11).…”
Section: Discussionmentioning
confidence: 99%
“…Although ␣2,3-or ␣2,6-linked sialic acid is considered the main IAV receptor and a key determinant for host and tissue tropism (44)(45)(46), sialidated-protein receptors are generally thought to facilitate virus entry (13). However, several lectin-type receptors (i.e., galactose-type lectin, mannose receptor, and DC-SIGN) that appear to bind IAV independently of sialic acid have been identified (47)(48)(49)(50). Accordingly, influenza virus can use multiple endocytic pathways to gain entry into host cells (7)(8)(9)11).…”
Section: Discussionmentioning
confidence: 99%
“…DC‐SIGN expressed in Lec2 Chinese hamster ovary (CHO) cells (glycosylation mutant deficient in CMP‐sialic acid transport) was shown to be an alternative receptor for glycans on the hemagglutinin (HA) of seasonal influenza A virus (H3N2) and A/PR/8/34 (PR8, H1N1) . Although, Hillaire et al have suggested that DC‐SIGN is a receptor of the A (H1N1) pdm09 subtype (A/Netherlands/602/09) , definitive evidence for the same is still awaited.…”
mentioning
confidence: 99%
“…CHO-ctrl, Lec2-ctrl, Lec2-Lg, Lec2-Lg P23I, and Lec2-⌬Lg cells (5 ϫ 10 4 cells/250 l) were seeded into eight-well chamber slides (Lab-Tek, Nunc, Denmark), cultured overnight, and infected with 10 7 PFU of IAV (corresponding to a multiplicity of infection [MOI] of 80), and the percentage of IAV-infected cells was determined as described previously (5,6,9). Briefly, after overnight culture, cell monolayers were washed and incubated with IAV or RSV in serum-free medium for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The macrophage mannose receptor (MMR) and macrophage ga-lactose-type lectin (MGL) have been implicated as receptors for infectious entry of IAV into murine M (5-7), and human DC-SIGN has been reported to bind to IAV, resulting in enhanced infection of host cells (8)(9)(10). MMR, MGL, and DC-SIGN are C-type lectin receptors (CLRs) that express a conserved carbohydrate recognition domain that binds to derivatives of mannose (for MMR and DC-SIGN) or galactose (for MGL), and these sugars are commonly expressed on the surface of a range of pathogens, including viruses (11).…”
mentioning
confidence: 99%